The Legal Structure of Political Parties in the Kurdistan Region-Iraq: An Analytical Study in the Law No. 17 of 1993 as Amended - Kareem, Zana Raouf Hama (Journal of Legal and Political Studies, 2014)
This study looking for the roots of legal political parties in the Kurdistan Region of Iraq through the study of the legal structure in light of the political conditions that prevailed in the Kurdistan Region - Iraq . and have proven experience that the ruling parties and the list since ancient times (it mean present in the political arena ahead of the 1993 Act) and modern ones, are the forces most of them are not governed by the law of the parties to resolve their internal problems or problems with the other parties, but turn some of them to the rules and regulations of their own compatible with its own objectives, programs and strategies in the areas of political and social, which means that most of the parties look at the political life of own private corner, without consideration of the controls legal protector of the life of political and party pluralism in the country, so it looks like it does not see the importance of the application of the law of parties at this stage they do not enforce the law, but trying to apply its own . Knowing that the law reflects the (theoretically) about the perceptions of the people of the mechanisms of action of political parties, and the rules of procedure of the political parties, it reflects the parties ' perceptions of the mechanisms regulating the work of the community, and there is great difference between the two concepts.
Keywords: political parties; strategie; Regulations; Internal problems